1978
DOI: 10.1111/j.1432-1033.1978.tb12283.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP‐Binding Proteins: Inverse Relationship with Estrogen‐Receptors in Hormone‐Dependent Mammary Tumor Regression

Abstract: Dimethylbenzanthracene-induced rat mammary carcinomas possess activities binding cyclic adenosine 3': 5'-monophosphate (CAMP) and estrogen. When dimethylbenzanthracene-induced tumors regress after ovariectomy of the host, a change in the specific binding of CAMP and estrogen occurs in the tumors. Six days after ovariectomy, CAMP binding increases 5-fold in the nuclei and 2-fold in the cytosol of tumors, while nuclear and cytoplasmic estrogen binding decreases by 80 and 50 %, respectively. These changes in acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Previous studies in patients with breast cancer (Taylor et al, 1982;Hamm & Allegra, 1988;Toma et al, 1986) and in experimental animals (Vignon & Rochefort, 1976;Hawkins et al, 1977b;Cho-Chung et al, 1978) have shown a decrease in receptor concentration after endocrine manipulation or, as in the present study, no consistant change (Hull et al, 1983;Mobbs et al, 1987). The conflicting results,in human breast cancer may derive from the inclusion of patients on tamoxifen (Taylor et al, 1982), which causes a marked apparent reduction in ER concentration (this study and Hull et al, 1983) or from the difficulties in comparing different tumour deposits (Taylor et al, 1982;Hamm & Allegra, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in patients with breast cancer (Taylor et al, 1982;Hamm & Allegra, 1988;Toma et al, 1986) and in experimental animals (Vignon & Rochefort, 1976;Hawkins et al, 1977b;Cho-Chung et al, 1978) have shown a decrease in receptor concentration after endocrine manipulation or, as in the present study, no consistant change (Hull et al, 1983;Mobbs et al, 1987). The conflicting results,in human breast cancer may derive from the inclusion of patients on tamoxifen (Taylor et al, 1982), which causes a marked apparent reduction in ER concentration (this study and Hull et al, 1983) or from the difficulties in comparing different tumour deposits (Taylor et al, 1982;Hamm & Allegra, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In experimental animals, cyclic AMP binding proteins are implicated in the growth of mammary tumours (Cho-Chung, et al, 1978b;Bodwin, et al, 1980;Bodwin et al, 1981). The corresponding evidence in human breast cancers has yet to be fully documented.…”
mentioning
confidence: 99%
“…It may be, however, that there are acute, more specific changes across a tumour. These may be similar to the rapid, inverse changes in cyclic AMP binding activity and oestrogen receptor concentration which occur during the regression of hormone-dependent mammary tumours in the rat (Cho-Chung et al, 1978).…”
mentioning
confidence: 60%
“…Additional assessment of progesterone receptor activity has been reported to increase further the accuracy of selecting patients for hormonal therapy (Horrowitz et al, 1975;Knight et al, 1980). More recently, studies of rat mammary tumours have shown that there seems to be an antagonistic action between oestrogen receptor activity and cyclic AMP binding proteins (subunits of the enzyme protein kinase) such that hormone-dependent tumours have high oestrogen receptor and low cyclic AMP-binding activities (Cho-Chung et al, 1978). Preliminary studies indicate that this activity also may be of prognostic significance in human breast cancers (Miller et al, 1983).…”
mentioning
confidence: 99%